Investigation of the liquid water distributions in a 50 cm2 PEM fuel cell: Effects of reactants relative humidity, current density, and cathode stoichiometry. (15th March 2015) - Iranzo, Alfredo; Boillat, Pierre; Biesdorf, Johannes; Salva, Antonio
Abstract: A 50 cm 2 commercial PEM fuel cell has been used to investigate the effects of a set of different operating conditions on the resulting liquid water distributions in the cell. A comprehensive matrix of operating conditions was analyzed, varying the reactants relative humidity (anode and cathode), cathode stoichiometry, and cell current density. Neutron imaging was used to determine the liquid water distributions within the cell for each operating condition. The obtained neutron radiographs were post-processed and analyzed in order to assess the effects of the different operating conditions. Cell voltage and cell resistance (High Frequency Resistance) were also monitored during the experiments and included in the analysis. Overall, the well-known water distributions corresponding to serpentine flow fields were observed, featuring a progressive water accumulation along the gas flow and towards the outlet port. Cathode channels were showing water accumulation. It was found that the cathode relative humidity had a much larger effect on the cell water content and overall performance than the anode relative humidity for this particular cell. Highlights: Neutron radiographs were used to study the water distribution in a 50 cm 2 PEMFC. A matrix of relative humidity, current density, stoichiometry, was investigated. Cathode RH was found to have a larger impact than anode RH for the MEA used (N117).